HUBUNGAN MOTIVASI PERAWAT DENGAN PELAKSANAAN DISCHARGE PLANNING DI RUANG RAWAT INAP RSM SITI KHODIJAH GURAH KABUPATEN KEDIRI - Fresty Africia; Suci W. Wahyuningsih (JURNAL SABHANGA, 2020)
Introduction : Discharge planning is the planning of returned patient with the aim to increase patient and family independence, reduce the risk of reccurence, the severity of the disease, even death. This discharge planning should be done by the nurse. Many factors that influence discharge planning by nurse one of them motivation. This study aimed to determine the correlation between nurses’ motivation and the implementation of discharge planning in the inpatient room at RSM Siti Khodijah, Gurah, Kediri Regency. Methods : This study used analytic with cross sectional approach, the number of population were 30 respondents, in the wich taken by using total sampling, taken 30 of the total population. The data collection used questionnaires of motivation of the nurse and questionnaires of discharge planning implementation. Result : The result from spearman rank test relevated that p (0,002) < (0,05). It means that Ho was rejected that there was an correlated nurses’ motivation and the implementation of discharge planning. Conclusion : Nurses with great motivation will make the discharge planning runs well.